2018
DOI: 10.1039/c8tc00582f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the emission spectrum of highly stable cesium lead halide perovskite nanocrystals through poly(lactic acid)-assisted anion-exchange reactions

Abstract: Emission tunable CsPbX3 NCs with high QY and stability were synthesized via PLA-assisted anion-exchange reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…[ 337 ] Poly(lactic acid) has also been used as a ligand to facilitate Br – to Cl – anion exchange in CsPbBr 3 NCs using a chloride‐containing solvent as a halide source. [ 338 ] Specifically, the carboxyl groups of poly(lactic acid) first bind to the Pb 2+ in the perovskite structure, freeing H + which can subsequently react with the chloroform solvent to break CCl bonds. [ 338 ] Furthermore, the free hydroxyl group of the poly(lactic acid) can form hydrogen bonding interactions with the amine ligands and reduce their local concentrations, allowing for the Cl – ions to absorb onto the NC surface more readily.…”
Section: Role Of Surface Ligands In Reactions With Lhp Ncs and Lhp Nc Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 337 ] Poly(lactic acid) has also been used as a ligand to facilitate Br – to Cl – anion exchange in CsPbBr 3 NCs using a chloride‐containing solvent as a halide source. [ 338 ] Specifically, the carboxyl groups of poly(lactic acid) first bind to the Pb 2+ in the perovskite structure, freeing H + which can subsequently react with the chloroform solvent to break CCl bonds. [ 338 ] Furthermore, the free hydroxyl group of the poly(lactic acid) can form hydrogen bonding interactions with the amine ligands and reduce their local concentrations, allowing for the Cl – ions to absorb onto the NC surface more readily.…”
Section: Role Of Surface Ligands In Reactions With Lhp Ncs and Lhp Nc Processingmentioning
confidence: 99%
“…[ 338 ] Specifically, the carboxyl groups of poly(lactic acid) first bind to the Pb 2+ in the perovskite structure, freeing H + which can subsequently react with the chloroform solvent to break CCl bonds. [ 338 ] Furthermore, the free hydroxyl group of the poly(lactic acid) can form hydrogen bonding interactions with the amine ligands and reduce their local concentrations, allowing for the Cl – ions to absorb onto the NC surface more readily. [ 338 ] Tetrabutylammonium p ‐toluene sulfonate and sodium dodecylbenzene sulfonate were added to a colloidal solution of CsPbBr x Cl 3− x NCs to achieve either Cl‐ or Br‐rich NCs, without the need for a halogenated solvent.…”
Section: Role Of Surface Ligands In Reactions With Lhp Ncs and Lhp Nc Processingmentioning
confidence: 99%
“…Chen et al demonstrated a facile solvothermal method for preparing CsPbX 3 PNCs with adjustable optical properties [ 18 ]. Additionally, Li's group reported a poly(lactic acid)-assisted anion-exchange method using a microreactor for tuning the emission spectra of CsPbX 3 PNCs from green to near-ultraviolet, which might be applicable for mass production [ 19 ]. Besides, great efforts have been made to prepare PNCs through the chemical transformation of pre-synthesized PNCs [ 20 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further improving the color gamut of LEDs is a hot spot for future commercial competition [14,15]. As a new type of luminescent material, quantum dots (QDs) are quite promising owing to their narrow half-peak width down to 30 nm, wide excitation wavelength, high color purity, and tunable emission [16,17].…”
Section: Introductionmentioning
confidence: 99%